PENYEBAB KURANG TERWUJUDNYA PENGARUH CONSTRUCTIVE ENGAGEMENT BALI DEMOCRACY FORUM TERHADAP PROSES TRANSISI DEMOKRATIS MYANMAR - Satrio Adjinegoro; Ika Riswanti Putranti; Marten Hanura (Journal of International Relations, 2023)
Myanmar’s military regime, namely Tatmadaw, has taken over political influence for a lengthy amount of time, whether directly or indirectly. On the 1st February 2021, Tatmadaw launched a coup to once again take over leadership after denouncing the election results won by the National League for Democracy. With Tatmadaw back in leadership, democratization in Myanmar not only regressed, but also proved difficult to return to its original state. Additionally, Myanmar still has not been fully democratic even though it has participated in the Bali Democratic Forum because of Tatmadaw’s large dominance. After the coup was launched in 2021, Myanmar was not invited to BDF’s 14th meeting.This research will explain the effects of BDF’S Constructive Engagement on Myanmar’s democratic transition process. This research will use qualitative and explanative methods, which means that it will answer the research question using narrations and relevant data. This research will also use Darren Hawkins’ theory of democratization with the assistance of Huntington and McFaul. By using these theories, the answer found is that the effects of BDF on Myanmar’s democratic transition have not manifested because most of BDF’s recommendations are aimed towards the governments, but not towards the civil society.